Inovasi Pemerintah Desa Dalam Pencegahan dan Penanganan Dampak Covid-19 di Desa Guwosari, Kabupaten Bantul - Erni Saharuddin (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The Covid-19 pandemic has had a huge impact on various sectors. This requires preventive measures as well as handling the impacts, so that innovative programs from the village government are needed in these conditions. The purpose of this study is to examine the innovations of the Guwosari village government in preventing and handling the impact of COVID-19. The research method used is descriptive qualitative, with data collection methods, in-depth interviews, observation and documentation. The results showed that the government of Guwosari Village had carried out several innovative programs; First, optimizing the use of digital platforms to provide education and also disseminate information regarding the steps to prevent and treat COVID-19. Second, the Gogrok Covid Program, the third the Jogo Tonggo Program to help the community during the pandemic, fourth, the Shelter Sehat Guwosari and finally the Distribution of BLT Village Funds using the pasardesa.id platform. The obstacles faced include, among others, there are residents who do not comply with health protocols and there are still rules regarding the arrival of residents from the city, as well as not optimal updating of data on social media.